2018
DOI: 10.1002/ece3.4402
|View full text |Cite
|
Sign up to set email alerts
|

Moose movement rates are altered by wolf presence in two ecosystems

Abstract: Predators directly impact prey populations through lethal encounters, but understanding nonlethal, indirect effects is also critical because foraging animals often face trade‐offs between predator avoidance and energy intake. Quantifying these indirect effects can be difficult even when it is possible to monitor individuals that regularly interact. Our goal was to understand how movement and resource selection of a predator (wolves; Canis lupus) influence the movement behavior of a prey species (moose; Alces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 89 publications
3
15
0
1
Order By: Relevance
“…Our findings are supported by recent studies showing that human-modified attributes and environmental factors are more important for moose abundance and browsing damage than wolf presence and time since wolf territory establishment (Gicquel et al, 2020). These results contrast with studies from protected areas where wolves have both density and behaviorally mediated effects on lower trophic levels (Fortin et al, 2005;Ripple and Beschta, 2012;Ripple et al, 2015;Ditmer et al, 2018). In protected areas such as Yellowstone National Park, there is often little to no anthropogenic activity and therefore, the relative importance of wolves to shape the dynamics and functions of an ecosystem is potentially higher (Mech, 1966(Mech, , 2013McLaren and Peterson, 1994;Berger et al, 2001a;Terborgh and Estes, 2010;Kuijper et al, 2016).…”
Section: Browsing Damagesupporting
confidence: 80%
See 1 more Smart Citation
“…Our findings are supported by recent studies showing that human-modified attributes and environmental factors are more important for moose abundance and browsing damage than wolf presence and time since wolf territory establishment (Gicquel et al, 2020). These results contrast with studies from protected areas where wolves have both density and behaviorally mediated effects on lower trophic levels (Fortin et al, 2005;Ripple and Beschta, 2012;Ripple et al, 2015;Ditmer et al, 2018). In protected areas such as Yellowstone National Park, there is often little to no anthropogenic activity and therefore, the relative importance of wolves to shape the dynamics and functions of an ecosystem is potentially higher (Mech, 1966(Mech, , 2013McLaren and Peterson, 1994;Berger et al, 2001a;Terborgh and Estes, 2010;Kuijper et al, 2016).…”
Section: Browsing Damagesupporting
confidence: 80%
“…A recent study found that moose browsing damage on Scots pine in south-central Sweden was higher inside wolf territories than outside (Gicquel et al, 2020). These results contrast with several studies of wolf-moose-plants systems in North America (Fortin et al, 2005;Ripple and Beschta, 2012;Ditmer et al, 2018). Such a difference may be explained by different degrees of anthropogenic impact in these systems (Kuijper et al, 2016), which may change or reduce the ecological effects of wolves on other trophic levels.…”
Section: Introductionmentioning
confidence: 71%
“…Thus the situation has been similar to that in our study system. Ditmer et al (2018) suggested that antipredator behaviors like increased movement rates could reduce the time available to critical activities like foraging, breeding and finding thermal shelter and are therefore likely to involve costs to moose. Therefore it seems plausible that these behaviors will be preserved only in conditions where they are regularly needed.…”
Section: Discussionmentioning
confidence: 99%
“…The antipredator behaviors may impose tradeoffs for the prey animals such as forcing prey to forage in safer but possibly nutritionally lower quality habitats and decreasing the time spent foraging. As a consequence the energy intake and condition of the prey animals may decrease (Ditmer et al 2018). When affecting the amount and distribution of plant consumption, the behavioral modifications of foraging prey may have effects also on community level i.e.…”
mentioning
confidence: 99%
“…Ze kunnen dichtheden van grote herbivoren reduceren (Ripple & Beschta, 2012), waardoor de kans op aanrijdingen met deze hoefdieren afneemt (Mech, 2017). Anderzijds verandert het habitatgebruik van hoefdieren in de aanwezigheid van wolven, zoals blijkt uit veranderingen in vegetatie als gevolg van veranderingen in graasdruk (Smith & Ferguson, 2012;White et al, 2012;Ditmer et al, 2018). Dit kan, in potentie, leiden tot het frequenter of juist minder frequent oversteken van wegen door hoefdieren, maar hier zijn in Nederland nog geen aanwijzingen voor gevonden.…”
Section: De Ontwikkelingen Inunclassified